Growth curves and nutritional requirements for maintenance of asymptotic weight of Nellore cattle - de Arruda, Rosana; Souza, Júlio; Jardim, Rodrigo José; Ferraz Filho, Paulo; Silva, Luiz Otávio (Revista Ciência Agronômica, 2018)
The objective of this study was to evaluate the growth curve of Nellore cattle raised in the Pantanal, Mato Grosso do Sul, in different groups of size (weight), sex, and birth season, as well as to estimate the nutritional requirements for maintenance of the asymptotic weigh. The nonlinear models were adjusted using the Gauss-Newton method, with information on weight and age of animals within each (total, upper, and middle) group. The asymptotic weight was influenced by sex (P